Distributions of sum, difference, product and quotient of independent noncentral beta type 3 variables (2013)
ABSTRACT: Let X and Y be independent random variables, X having a gamma distribution with shape parameter a and Y having a non-central gamma distribution with shape and non-centrality parameters b and δ, respectively. Define Z = X/(X + 2Y ). Then, the random variable Z has a non-central beta type 3 distribution, Z ∼ NCB3(a, b; δ). In this article we derive density functions of sum, difference, product and quotient of two independent random variables each having non central beta type 3 distribution. These density functions are expressed in series involving first hypergeometric function of Appell.